Assessment of outcome of trial of labour after caesarean in a tertiary hospital based setting: prospective observational study - Bhardwaj, Mahak; Gainder, Shalini; Chopra, Seema; Bagga, Rashmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Aim of this study was to determine the success rate of vaginal birth after caesarean (VBAC) in Indian women, identify the factors that predict its success, and assess the maternal and neonatal outcomes following a trial of labour after caesarean (TOLAC). Methods: A prospective observational study involving women with one previous lower segment caesarean section (LSCS) who were admitted for TOLAC between January 2019 and June 2020 at Department of Obstetrics and Gynaecology, Post Graduate Institute of Medical Education and Research, Chandigarh, India. There were 124 women with previous LSCS who opted for TOLAC. Results: During the study period, 124 women with previous LSCS who opted for TOLAC were included, of whom 68 (54.8%) had successful VBAC and 56 (45.2%) had failed TOLAC. The induction of labour (IOL) rate in the study was 69.4%, and 30.6% of women had spontaneous onset of labor. VBAC rates were significantly higher in women who went into labour spontaneously (84.2% vs. 15.8%). Maternal complication rates were comparable, whereas the neonatal complication rate was significantly higher in neonates born by CS (51.7% vs. 30.8%), with a greater incidence of low birthweight (LBW) and transient tachypnea in the newborn (TTNB). Conclusions: TOLAC can be considered a safe option for women with a previous caesarean when combined with vigilant and stringent labour monitoring, despite the use of IOL agents.